THE EFFECT OF APPLYING SOMATIC AUDITORY VISUAL INTELLECTUAL (SAVI) METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING REPORT TEXT - Harnoi Asrin Lumban Gaol; Masitowarni - Siregar (TRANSFORM : Journal of English Language Teaching and Learning, 2014)
This study deals with the effect of applying Somatic Auditory Visual Intellectual (SAVI) method on students’ achievement in writing report text. The objective of the study is to find out whether SAVI method significantly affects the students’ achievement in writing report text or not. This study was conducted by using experimental design. The population of the study was the students of grade XI of SMA Swasta Bintang Timur 1 Balige in the academic year 2013/2014, where there were 4 classes of XI Science (IA) and there were two classes were selected as the sample by applying random sampling. The sample was divided into two groups. The Experimental group (XI.IA 3) was taught by applying SAVI method, while the control group (XI.IA 2) was taught by applying conventional method. The data of the study were obtained from the students’ score of writing test. To determine the reliability of the test, the writer used Pearson Moment Product formula. Based on the data calculation showed that the coefficient of reliability of the test was 0.96. It showed that the test was reliable and the reliability was high. There were two data used in this study. They were pre-test and post-test. The data were analyzed by applying t-test formula. After analyzing the data, the result of the study showed that t-observed (5.091) was higher than t-table (1.990) (t-observed ˃ t-table) at the level of significance of α = 0.05 and at the degree of freedom (df) = 82. It can be concluded that applying SAVI method significantly affects on the students’ achievement in writing report text or in other words the hypothesis is accepted.   Key Words     : Students’ Achievement, Writing, Report Text, SAVI Method.